Mathematics, Technology Interventions and Pedagogy- Seeing the Wood From the Trees - Bray, Aibhin (SCITEPRESS - Science and Technology Publications, 2013)
This research explores recent technological interventions in mathematics education and examines to what extent these make use of the educational opportunities offered by the technology and appropriate pedagogical approaches to facilitate learning. In an attempt to answer this question, a systematic literature review has been carried out, and a classification is presented that categorises the types of technology as well as the pedagogical foundations of the interventions in which those technologies are used. The potential of technology to fundamentally alter how mathematics is experienced is further investigated through the lens of the SAMR hierarchy, which identifies four levels of technology adoption: substitution, augmentation, modification and redefinition. The results of the research will be beneficial for guiding teaching in a technology rich environment, offering the potential to improve mathematics education
Proceedings of the 5th International Conference on Computer Supported Education
5th International Conference on Computer Supported Education (CSEDU 2013)
PUBLISHED
Aachen, Germany
Keywords: Mathematics; Education; Technology; Classification